The Effect of Integrated Learning on Increasing Biology Knowledge and English Language Competency in Class XII IPA on the Entrepreneurial Attitudes of MAN Insan Cendekia Jambi Students for the 2023/2024 Academic Year - Aty Mulyani; Didik Setiaji; Muhammad Bustanul Arifin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explains the importance of integrated learning. So the integration of Biology, English and Entrepreneurship subjects is very useful for developing entrepreneurial character, as a preparation for their future lives. Mastery of biological material and its application in life will be very useful for developing students' entrepreneurial attitudes. The results of this integrated learning show that 100% of students succeeded in understanding the material on plant growth and development. Based on previous experience, the results of germination cannot be successful. The germination process failed twice. This happens because they do not yet understand biological knowledge on the subject of plant growth and development. Based on facts after understanding the material on plant growth and development. all 12th grade science 2 students can achieve very well. The sprouting process was very successful. The sprouts look clean and nice. Students applying English language competency can be seen from the description of the results of germination practice. Explanations ranging from tools and materials, manufacturing procedures, to processes are explained using clear and correct English. Presented in front of the class and reported in writing. Therefore, in terms of language and communication skills, class 12 IPA 2 students are very good. Then, entrepreneurially, the sprouts are made, packaged and sold. All sold out. Starting from a nominal amount of 15 thousand rupiah, and using the available tools to support the germination process for 3 days. In conclusion, the integrated learning model of collaboration is very useful in forming the entrepreneurial attitude of class XII students at MAN Insan Scholar Jambi.